The American tradition in literature (McGraw-Hill, 1994)
Widely known as the anthology that best meshes tradition with innovation, The American Tradition in Literature enters its eighth decade of leadership among textbook anthologies of American Literature. Literary merit remains the guiding principle of selection; flexibility of organization, with Walt Whitman represented in both volumes, continues to be one of the text's hallmarks